4 - Graduates’ Perception of University Programmes and Their Relevance to Employment: University of Nairobi (1991 -1998): DOI: 10.4314/ad.v30i1.22213 - Kimani, Gerald Ngugi (Africa Development, 2005)
This paper reports a study to assess graduates' perception of the learning conditions and provisions at the University of Nairobi, Kenya. The study identified the jobs held by the graduates and the extent to which they use knowledge, attitudes and skills acquired during their study at the University of Nairobi in their present jobs. The sample consisted of 1,640 graduates drawn from 3,300 graduates of Bachelor of Education (Arts), Bachelor of Science and Bachelor of Commerce degree pro grammes who had completed their studies between 1991 and 1998. Questionnaires were sent to 1,400 graduates and some 240 others were administered directly to respondents. A total of 580 questionnaires were returned representing a return rate of 35.4 per cent. The findings show that overall the scope and coverage of the courses, teaching quality of lectures and contact with students were the most highly rated aspects of study conditions and provisions of the University of Nairobi. Counseling services, catering facilities on the campus and recreational facilities were the lowly rated aspects. About 61 per cent of graduates were employed in public sector while 37 per cent were in private sector. About 2 per cent were self employed. Of the surveyed graduates 72 per cent indicated that they used knowl edge and skills acquired at the university to a high or very high extent while 25 per cent indicated moderate use. Only 3 per cent responded to the contrary.